A Case Study of Loyola College Senior High School: Changes in The Learning Culture of An Excellent School - Nur Arifah; Ibrahim Bafadal; Raden Bambang Sumarsono (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2025)
This article describes the significant changes in the learning culture of Loyola College Senior High School Semarang. The research identified changes in organizational structure, work system and culture, pedagogical approach, and research culture in the educational institution. Data were collected through semi-structured interviews using snowball sampling with a key informant, namely the principal, observation, and document study. Analysis was carried out using the Miles and Huberman reduction, representation, and inference model. Meanwhile, triangulation of data sources was used to ensure validity. The results showed that the changes made included the adaptation of the organizational chart for more efficient management of human resources, the implementation of a more collaborative working system and a culture that supports innovation, a more open and inclusive approach to learning, and an increased research culture among teachers and students. The change process involved thoroughly evaluating the existing organizational structure, introducing new, more responsive working systems, empowering staff to implement innovative learning approaches, and adding infrastructure to support a strong research culture. Overall, these changes have positively impacted teachers and students, improving the quality of learning and strengthening the capacity of educational institutions to meet future challenges. The results of this study underline the importance of maintaining a culture of continuous education in educational institutions to respond to the needs of the times and prepare students for a dynamic future.